1997
DOI: 10.1016/s0735-1097(96)00424-x
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia and Mortality After the Mustard Procedure: A 30-Year Single-Center Experience

Abstract: Ongoing loss of sinus rhythm and late peaks in the risk of atrial flutter and death necessitate continued follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
241
2
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(263 citation statements)
references
References 20 publications
10
241
2
10
Order By: Relevance
“…14 There were 77 late deaths (16%), with unexpected sudden death occurring in 31 patients at a median of 3.2 years after the operation. 13 Sudden presumed arrhythmic death and myocardial failure were the most frequent causes of late death, a finding that agrees with other reports. 15 Atrial arrhythmias can precipitate a significant deterioration in systemic ventricular function, and, in general, sinus rhythm should be restored when possible.…”
Section: Arrhythmiassupporting
confidence: 90%
See 2 more Smart Citations
“…14 There were 77 late deaths (16%), with unexpected sudden death occurring in 31 patients at a median of 3.2 years after the operation. 13 Sudden presumed arrhythmic death and myocardial failure were the most frequent causes of late death, a finding that agrees with other reports. 15 Atrial arrhythmias can precipitate a significant deterioration in systemic ventricular function, and, in general, sinus rhythm should be restored when possible.…”
Section: Arrhythmiassupporting
confidence: 90%
“…[7][8][9][10] Sinus node dysfunction is common in adults, 11 and the cause is probably damage to the sinus node and atrial conduction tissue or interruption of sinus node blood flow at the time of operation. 12 In the series of 534 children by Gelatt et al, 13 sinus rhythm was present in 77% at 5 years and only 40% at 20 years. Fifty-three patients (11%) needed pacemaker implantation.…”
Section: Arrhythmiasmentioning
confidence: 96%
See 1 more Smart Citation
“…Survival functional status and quality of life of patients with transposition of the great arteries (TGA), after an atrial switch operation (Senning or Mustard procedure) are reported to be reasonably good after 2 decades of life [1][2][3][4][5][6][7][8]. However, in many cases, It's possible to detect the function of the systemic right ventricle deteriorates, severe tricuspid regurgitation develops or the patients suffer from arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Multiple mechanisms for RV dysfunction late after atrial switch have been postulated. Previously published nuclear medicine data have demonstrated both fixed and reversible perfusion defects in patients up to 25 years after atrial redirection surgery.…”
Section: Introductionmentioning
confidence: 99%